Explaining the Experiences of Health Care Providers During the COVID-19 Pandemic: A Qualitative Study - Faeze Kobrai-Abkenar; Parand Pourghane; Fatemeh Jafarzadeh-Kenarsari (Kerman University of Medical Sciences, 2023)
Background: Healthcare providers in different countries have different experiences during epidemic conditions based on their nursing resources and healthcare systems and the cultural norms of the community. The present study aimed to explore the experiences of healthcare providers during the COVID-19 pandemic.Methods: This qualitative study was conducted on 36 medical personnel from eastern Guilan in the north of Iran. The participants were selected via purposive sampling. The data were collected through semi-structured interviews. The interviews continued until data saturation. Data analysis was performed using conventional content analysis, simultaneous with data collection.Results: Data analysis revealed three main categories and 10 subcategories: peaceful coexistence (scientific-professional development, enhanced emotional proximity, and resilience in critical situations), the outburst of despair (exhaustion in clinical settings, annoying obsessions, ambivalent decision making, and excessive fear), and in the shadow of sorrow (the shadow of depression, painful public rejection, and in financial distress).Conclusion: An analysis of the participants' experiences during the COVID-19 pandemic revealed three main themes: peaceful coexistence, the outburst of despair, and in the shadow of sorrow. Paying attention to the physical, psycho-social, emotional, and financial challenges and needs of healthcare providers, especially during the COVID-19 pandemic, is an undeniable necessity and requires the full attention and support of the authorities and the community.